PEMODELAN KASUS GIZI BURUK PADA BALITA DI PROVINSI BALI TAHUN 2018 MENGGUNAKAN REGRESI SPLINE - DANGIN, NYOMAN KRISHNA PRATIWI; SRINADI, I GUSTI AYU MADE; SUMARJAYA, I WAYAN (E-Jurnal Matematika, 2021)
Malnutrition associated with an unusual condition of the patient's nutritional status because the body weight index and age are not suitable, where body weight should be positively correlated with age. According to data from the Bali Health Department, malnutrition cases found in 2016 is 3,4% while in 2017 it founded 3,8%. This research uses spIine regression with malnutrition cases of children under 5 years old in Bali Province. To compare basis truncated spIine and B-SpIine, this study using the minimum value of Generalized Cross Validation (GCV) and Mean Square Error (MSE) of each basis. B-SpIine quadratic modeI with four knots is the best model.